Feasibility study for removing calcified material using a planar rectangular ultrasound transducer - Damianou, Christakis A.; Couppis, Andreas (My University, 2016)
Background: The aim of the proposed study was to conduct a feasibility study using a flat rectangular (3 mm × 10 mm) MRI compatible transducer operating at 5.3 MHz for destroying calcified material in an in vitro model. The proposed method can be used in the future for treating atherosclerosis plaques of the coronary, carotid or peripheral arteries. Methods: The system was tested initially on calcium rods. Another test was performed in a hydroxyapatite–polylactide model. Results: A parametric study was performed where the mass of calcified material removed was studied as a function of intensity, pulse repetition frequency (PRF), duty factor (DF) and presence of bubbles. Conclusions: The amount of calcified material removed is directly related to the intensity, PRF and DF. It was found that the presence of bubbles accelerates the removal of calcified material. In order to ensure that pure mechanical mode ultrasound was used, the protocols were designed so that the temperature does not exceed 1 °C.
Keywords: Atherosclerotic; Plaque; Rabbit; Ultrasound